PENGARUH GOOD CORPORATE GOVERNANCE DAN STRUKTUR KEPEMILIKAN TERKADAP KINERJA PERUSAHAAN - Rizqi Waluya Ningsih; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2019)
ABSTRACTThis research aims to determine the effect of good corporate governance and ownership structure on firm performance. This study uses secondary data form financial reports obtained from BEI. The sample selection is done by purposive sampling method. Data analysis using the classical assumption test and multiple linear regression. Indicators of good corporate governance in this study is independent commissioner, board of director, and audit committee. Indicators of ownership structure in this study is managerial ownership and institutional ownership. Firm performance indicators, namely ROE (Return On Assets). The study population was a company BUMN listed on Indonesia Stock Exchange in 2015-2017Keyword: corporate governance, institutional ownership, managerial ownership, independent commissioner, board of director, audit committee, ROE.